Correlates of residents' enrolment intention toward inclusive commercial health insurance in China: involvement, perceived benefit, perceived sacrifice, and government participation - Shen, Tianyi; Wang, Yinuo; Xie, Jinping; Han, Xu; Shao, Rong; Jiang, Rong (Frontiers in Public Health, 2023)
Background As an application of inclusive finance in health insurance, inclusive commercial health insurance (ICHI) is a new public-private partnership-based health insurance scheme and has been vigorously promoted by the Chinese government in recent years to develop China Multi-level Health Insurance System, a system that aims to seek a mix of public and private sources to provide more affordable financial protection to all levels of society in line with their needs. However, the overall enrolment of ICHI scheme is still at a low level, and little is known about what influences residents' enrolment intentions. The aim of this study was to examine the multidimensional factors influencing residents' behavioral intentions and to develop a multivariate conceptual model to explore the psychographic process in the formation of enrolment intention. Methods The empirical data used for model validation were obtained from a cross-sectional study conducted in Nanjing, China, a representative pilot city of ICHI scheme in 2022. Exploratory factor analysis, ANOVA, standard multiple regression, and hierarchical multiple regression were mainly employed for hypothesis testing. Results The findings revealed that involvement, perceived benefit, and perceived sacrifice are all crucial psychographic process factors in the formation of residents' enrolment intentions. Government participation positively moderates the influence path of “perceived benefit—enrolment intention” but negatively moderates the path of “perceived sacrifice—enrolment intention”. Moreover, it was discovered that perceived benefit mediates the effect of involvement on enrolment intention, while perceived sacrifice does not. Conclusions Improving residents' perceived benefit and involvement degree of the product, as well as reducing their perceived sacrifice, are both key to increasing their enrolment intentions. This study also points out that one of the main dilemmas in the current development of ICHI scheme is the low level of involvement among residents, and that optimizing the product design to make it more relevant to residents' lives is a more beneficial strategy to increase overall involvement.